2019
DOI: 10.1017/s0954579419000555
|View full text |Cite
|
Sign up to set email alerts
|

Early life stress, cortisol, frontolimbic connectivity, and depressive symptoms during puberty

Abstract: Early life stress (ELS) is a risk factor for the development of depression in adolescence; the mediating neurobiological mechanisms, however, are unknown. In this study, we examined in early pubertal youth the associations among ELS, cortisol stress responsivity, and white matter microstructure of the uncinate fasciculus and the fornix, two key frontolimbic tracts; we also tested whether and how these variables predicted depressive symptoms in later puberty. A total of 208 participants (117 females; M age = 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 85 publications
2
36
0
Order By: Relevance
“…A nuanced understanding of how early experiences alter structural brain development is critical to elucidating the mechanisms by which childhood adversity confers risk for psychopathology, and protective environmental factors buffer that risk. Early adverse experiences have been shown to disrupt neurodevelopment on a cellular level ( Abbink et al, 2019 ; Bath et al, 2016 ; Bordner et al, 2011 ; Johnson and Kaffman, 2018 ), and a growing literature has identified alterations in structural brain features such as gray matter volume ( De Bellis et al, 1999 ; Hair et al, 2015 ; Hanson et al, 2012 ; Hodel et al, 2015 ; Kribakaran et al, 2020 ; Mackes et al, 2020 ; McEwen, 2016 ; Noble et al, 2015 ; Sheridan et al, 2012 ; Teicher et al, 2016 ; Tottenham et al, 2010 ), cortical thickness ( Gold et al, 2016 ; Kelly et al, 2013 ; Lim et al, 2018 ; McLaughlin et al, 2014 ; Monninger et al, 2019 ), white matter tract integrity ( Bick et al, 2015 ; Hanson et al, 2013 ; Ho et al, 2017 ; Howell et al, 2013 ; Kircanski et al, 2019 ), and myelination ( Bath et al, 2016 ; Bordner et al, 2011 ; Juraska and Kopcik, 1988 ; Makinodan et al, 2012 ) following adversity.…”
Section: Introductionmentioning
confidence: 99%
“…A nuanced understanding of how early experiences alter structural brain development is critical to elucidating the mechanisms by which childhood adversity confers risk for psychopathology, and protective environmental factors buffer that risk. Early adverse experiences have been shown to disrupt neurodevelopment on a cellular level ( Abbink et al, 2019 ; Bath et al, 2016 ; Bordner et al, 2011 ; Johnson and Kaffman, 2018 ), and a growing literature has identified alterations in structural brain features such as gray matter volume ( De Bellis et al, 1999 ; Hair et al, 2015 ; Hanson et al, 2012 ; Hodel et al, 2015 ; Kribakaran et al, 2020 ; Mackes et al, 2020 ; McEwen, 2016 ; Noble et al, 2015 ; Sheridan et al, 2012 ; Teicher et al, 2016 ; Tottenham et al, 2010 ), cortical thickness ( Gold et al, 2016 ; Kelly et al, 2013 ; Lim et al, 2018 ; McLaughlin et al, 2014 ; Monninger et al, 2019 ), white matter tract integrity ( Bick et al, 2015 ; Hanson et al, 2013 ; Ho et al, 2017 ; Howell et al, 2013 ; Kircanski et al, 2019 ), and myelination ( Bath et al, 2016 ; Bordner et al, 2011 ; Juraska and Kopcik, 1988 ; Makinodan et al, 2012 ) following adversity.…”
Section: Introductionmentioning
confidence: 99%
“…One possibility is therefore that chronically elevated cortisol in childhood may lead to accelerated myelination in certain white matter tracts. Indeed, some work has linked higher cortisol to increased FA in other white matter tracts such as the uncinate fasciculus (Kircanski et al., 2019; Dennison et al., 2019; though see Lichtin et al., 2021, which linked material deprivation to lower FA in this tract). In the future, longitudinal research is needed to elucidate developmental mechanisms and discern how stress physiology relates to changes in white matter organization over time.…”
Section: Discussionmentioning
confidence: 99%
“…Although most studies have used clinical samples and compared those with and without an internalizing disorder, some studies have focused on typically developing children and adolescents (Mohamed Ali, Vandermeer, Sheikh, Joanisse, & Hayden, 2018). It is also noteworthy that some studies have found that higher FA in the UNC is associated with adolescent depression (Aghajani et al., 2014; Bracht, Linden, & Keedwell, 2015; Kircanski et al., 2019).…”
Section: Introductionmentioning
confidence: 98%
“…We expected that material hardship would be associated with UNC FA, medial OFC surface area, and amygdala volume, which would in turn be associated with internalizing symptoms. Directionality could not be specified for these hypotheses due to inconsistencies in the existing research, as detailed above (Dennison et al., 2019; Dufford & Kim, 2017; Kircanski et al., 2019; LeWinn et al., 2014). Finally, we expected these associations to be stronger in girls compared to boys (Hodes & Epperson, 2019; Oldehinkel & Bouma, 2011).…”
Section: Introductionmentioning
confidence: 99%